The Junior Eysenck Personality Inventory ratings of traumatized youth with and without PTSD. (October 2016) - Saigh, Philip A.; Hackler, Dusty; Yasik, Anastasia E.; McGuire, Leah A.; Bellantuono, Alessandro; Dekis, Constance; Durham, Katherine; Halamandaris, Phill V.; Oberfield, Richard A.
Abstract: The Junior Eysenck Personality Inventory ( JEPI ) scores of traumatized youth with or without PTSD were compared to the scores of a non-traumatized control group. It was observed that the PTSD group had significantly higher JEPI Neuroticism scores relative to the comparison groups. The JEPI Neuroticism scores of the traumatized group without PTSD and the non-traumatized controls were not significantly different. Nonsignificant differences were also evidenced between groups on the JEPI Extraversion and Lie scales. Highlights: PTSD was associated with neuroticism. Trauma exposure without PTSD was not associated with neuroticism. Extraversion did not differ between trauma groups with or without PTSD or controls.